Financial Analysis of Underpricing Levels in Companies Conducting IPO on the Indonesian Stock Exchange - Nugraheni, Isnawati; Sari, Shinta Permata (Universitas Muhammadiyah Surakarta, 2024)
Purpose: The phenomenon of underpricing does not only occur in Indonesia, but almost all over the world. The aim of this research is to establish the affect of financial ratios on the level of stock underpricing in firm conducting Initial Public Offering (IPO) and are recorded on the Indonesia Stock Exchange (IDX) for the term 2021-2023. Methodology: The technique of examination in this research is quantitative data examination application multiple linear regression. The purposive sampling method is used to select samples, and 94 companies are obtained that met the research criteria after outliers are made. The process of collecting secondary data is done through documentation studies. The data examination technique is assisted by the SPSS 26.00 software. Results: The analysis test results obtained that liquidity and financial leverage have no affect on the underpricing levels, whereas activity ratio and firm size have negative significant affect, but ROE tend a positive significant affects on the underpricing levels. The decrease in uncertainty by the company will also reduce the level of underpricing. Applications/Originality/Value: Many previous research have explore the factors that affect underpricing, but studies that specifically explore the role of financial ratios are still limited, especially for the post-2020 period. This research contributes to the literature by assure fresh empirical proof on the relationship between liquidity ratio (CR), financial leverage (DER), activity ratio (TATO), firm size (SIZE), and profitability (ROE) to underpricing which can then be adopt into advisement for investors, issuers, and underwriters in making decisions.